PowerShell and Python together : targeting digital investigations - Hosmer, Chet (Apress, 2019)
Chapter 3: PowerShell Scripting Targeting Investigation; Basic Facts About PowerShell Scripts; Example 1: The EventProcessor PowerShell Script; EventLog CmdLets; Retrieving More Specific Eventlog Information; Creating the Script; Step One: Define the Challenge; Step Two: Create the Script in Stages; Script Header; .Synopsis Section; .Description Section; .Parameters Section; .Examples Section; Parameter Definition; Local Variable Definition; CmdLet Pipeline Execution; EventProcessor Get-Help Result; EventProcessor Script Execution; Resulting Directory; HTML Output Report; Remote Access